Improving disseminated histoplasmosis diagnosis in HIV/AIDS patients in Suriname: The role of a urine lateral flow assay. - Lycke Woittiez; Stefan Vestjens; Terrence Mawie; Ed IJzerman; Pieter-Jan Haas; Ferry Hagen; Jimmy Roosblad; Stije Leopold; Maaike D van Schagen; Michèle van Vugt; Stephen Vreden (Public Library of Science (PLoS), 2024)
Histoplasmosis is a frequent cause of infections in people living with HIV/AIDS (PLWHA). This study introduces the application of a Histoplasma capsulatum urine antigen lateral flow assay (LFA) for diagnosing disseminated histoplasmosis in PLWHA in Suriname. The LFA's diagnostic accuracy was compared with the current diagnostic approach, aiming to assess whether this test resulted in improved early detection and management. Additionally, the prevalence of histoplasmosis among advanced stage HIV patients without clinical suspicion of infection was evaluated using the same LFA. In total, 98 patients were included in the study, of which 58 were classified as "possible disseminated histoplasmosis (DH)" based on clinical criteria and 40 as "controls". Of these possible DH cases, only 19 (32.7%) had a positive LFA. During the study, decisions for treatment were made without the treating physician being aware of the LFA result. Only 55% of the patients who started treatment for histoplasmosis based on clinical criteria had a positive LFA, and 21% of untreated patients had a positive LFA. This study shows that combining clinical signs with LFA results enhances diagnostic accuracy and is cost effective, resulting in better treatment decisions.